Higher Human T-Lymphotropic Virus Type 1 Subtype C Proviral Loads Are Associated With Bronchiectasis in Indigenous Australians: Results of a Case-Control Study. (28th May 2014) - Einsiedel, Lloyd; Cassar, Olivier; Goeman, Emma; Spelman, Tim; Au, Virginia; Hatami, Saba; Joseph, Sheela; Gessain, Antoine
Abstract : In this case-control study, HTLV-1 infection increased risk of bronchiectasis 1.84 times. HTLV-1 proviral loads for bronchiectasis patients were significantly higher than those of controls. HTLV-1 proviral loads correlated with the extent of radiologically determined pulmonary injury. Abstract: Background.  We previously suggested that infection with the human T-lymphotropic virus type 1 (HTLV-1) subtype C is associated with bronchiectasis among Indigenous Australians. Bronchiectasis might therefore result from an HTLV-1-mediated inflammatory process that is typically associated with a high HTLV-1 proviral load (PVL). Human T-lymphotropic virus type 1 PVL have not been reported for Indigenous Australians. Methods.  Thirty-six Indigenous adults admitted with bronchiectasis from June 1, 2008, to December 31, 2009 were prospectively recruited and matched by age, sex, and ethno-geographic origin to 36 controls. Case notes and chest high-resolution computed tomographs were reviewed, and pulmonary injury scores were calculated. A PVL assay for the HTLV-1c subtype that infects Indigenous Australians was developed and applied to this study. Clinical, radiological, and virological parameters were compared between groups and according to HTLV-1 serostatus. Results.  Human T-lymphotropic virus type 1 infection was the main predictor of bronchiectasis in a multivariable model (adjusted risk ratio [aRR], 1.84; 95% confidence interval [CI], 1.19–2.84; P = .006). Moreover, the median HTLV-1c PVL (interquartile range) for cases was >100-fold that of controls (cases, 0.319 [0.007, 0.749]; controls, 0.003 [0.000, 0.051] per 100 peripheral blood lymphocytes; P = .007), and HTLV-1c PVL were closely correlated with radiologically determined pulmonary injury scores (Spearman's rho = 0.7457; P = .0000). Other predictors of bronchiectasis were positive Strongyloides serology (aRR, 1.69; 95% CI, 1.13–2.53) and childhood skin infections (aRR, 1.62; 95% CI, 1.07–2.44). Bronchiectasis was the major predictor of death (aRR, 2.71; 95% CI, 1.36–5.39; P = .004). Conclusions.  These data strongly support an etiological association between HTLV-1 infection and bronchiectasis in a socially disadvantaged population at risk of recurrent lower respiratory tract infections.